Effectiveness of Healthy Menu Changes in a Nontrainee Military Dining Facility - Belanger, Bethany A.; Kwon, Junehee (My University, 2016)
The purpose of this study was to evaluate the impact of implementing the Initial Military Training (IMT) menu standards in nontrainee dining facilities (DFAC) on food selection, nutrient intake, and satisfaction of soldiers. Participants were recruited during lunch before and 3 weeks after the menu changes. Direct observations, digital photography, and plate waste methods were used to assess soldiers’ food selection and consumption, along with a survey assessing soldiers’ meal satisfaction under the two menu standards. Descriptive statistics and independent sample t-tests were used to summarize and compare the data. A total of 172 and 140 soldiers participated before and after menu changes, respectively. Soldiers consumed 886 kcals (38.6% from total fat and 11.2% from saturated fat) and 1,784 mg of sodium before the menu change. Three weeks after the change, all figures improved ( p < 0.01). The percentage of healthier food selections mirrored food items served at the DFAC and improved after the intervention ( p < 0.001). There were no differences observed in overall satisfaction and meal acceptability after the intervention. Our findings suggest implementing the Initial Military Training menu standards in nontrainee Army DFACs is feasible and has the potential to improve the overall healthfulness of soldiers’ food selection and consumption.
Citation: Belanger, B. A., & Kwon, J. (2016). Effectiveness of healthy menu changes in a non-trainee military dining facility. Military Medicine, 181(1), 82-89.